The Perspective of the Court of Cassation and the Problems Concerning the Expert System in the Light of the Relevant Judgements - Karaburun, Gökhan (The Bulletin of Legal Medicine, 2017)
Although the experts and the expert system are tools for assessing the evidence which directly affects “the right to fair trial”, it has become one of the major problems of the judiciary system since it has not been institutionalized yet. Even though the Law No: 6754 on Expert Report has been an important step towards institutionalization of the expert system, the main tool for judicial review in this field is, for sure, the judgments of the high courts.This article elaborates on the perspective of the Court of Cassation (CoC) regarding the expert system and legal status of the experts considering the criteria used in the judgments of the Court of Cassation, principles described by the Law No: 6754 and relevant regulation and various solutions occurred in practice.
Keywords: Judgments of the Court of Cassation; expert; report; law on experts